Spatial distribution of tuna larvae in the Gulf of Gabes (Eastern Mediterranean) in relation with environmental parameters - KOCHED, W.; HATTOUR, A.; ALEMANY, F.; GARCIA, A.; SAID, K. (Mediterranean Marine Science, 2013)
Spatial distribution and ecology of the larvae of three tuna species (Thunnus thynnus, Auxis rochei and Euthynnus alletteratus) were studied during an ichthyoplankton survey carried out in the Gulf of Gabes (Tunisia) in June and July 2009. A total of 80 stations, distributed on a regular sampling grid, were sampled. The main objectives of this survey were to provide information on tuna larvae distribution in the Gulf of Gabes in relation to the environmental parameters. Regarding small tunas, larvae of A. rochei (bullet tuna) showed the more widespread distribution, being found at both inshore and offshore stations. E. alletteratus (Atlantic black skipjack) larvae were mainly found at the inshore stations covering the wide continental shelf of this region. On the other hand, larvae of the large migratory tuna T. Thynnus (Atlantic bluefin tuna), were mainly recorded at offshore stations, suggesting that spawning possibly takes place mainly near the shelf break. Regarding the biological and physical parameters examined, our results indicate that tuna larvae were mainly collected in oligotrophic and mixed waters resulting from the confluence of surface water of recent Atlantic origin and resident surface Mediterranean waters, as shown by their preference for lower chlorophyll a concentrations (from 1.4 to 2.5 mg m-3) and moderate salinity values (between 37.35 and 37.75). Significantly, tuna larvae seemed to avoid the more eutrophic and saltier waters of the gulf situated very close to the coast and around Kerkennah and Djerba islands.